Review: Respon Fisiologis Ikan terhadap Lingkungan Hidupnya - Pane, Elya Putri; Arfiati, Diana; Apriliyanti, Fisma Josara (Jurnal Aquatik, 2023)
Fish need a specific environment as a habitat to grow and develop. Environmental conditions can change, so this becomes a challenge for fish to maintain homeostasis in the fish's body. Two factors influence the physiological condition of fish, namely internal and external factors. Information regarding fish physiology is needed as one of the factors that are the centre of attention in proper cultivation to support the productivity of commercial fish cultivation. Environmental changes such as pollution significantly affect the physiological condition of fish, and supplementing fish food can also support the fish's body metabolism. This article review study describes important factors that can influence the physiological response of fish and provides three case studies of commercially farmed fish when exposed to toxic substances or the provision of organic substances in feed. The data used is secondary data using journals from previous research and grouping topics regarding environmental factors and case studies on grouper fish in the Serranidae family.